(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The responsibilities of the late-medieval elites in stirring up conflict and the subsequent outbursts of violence, have long been contentious. The documents from the town of Pinerolo confirm the spread of aggressive behaviours among the wealthy population, but they also give an insight on the hazards inherently connected to such behaviours. Overall, the adoption of pragmatic strategies by the offenders and the victims both, combined with the growing intervention of the public authorities, kept disagreements and aggressions from tearing the social order apart.